PENGALAMAN PENGASUH DALAM MERAWAT LANSIA DENGAN PENYAKIT KRONIS REMATIK DI WILAYAH JANGKAUAN LKS LU MANDAR INDONESIA DI DESA BUKU - Fredy Akbar; Hamdan Nur; Hardika Hardika (Jurnal Kesehatan Masyarakat (Undip), 2022)
The aging process is a life cycle characterized by the decline in various organ functions in the body which is marked by the susceptibility of the body to various disease attacks. As for these changes affect the deterioration of physical health which in turn will affect susceptibility to disease. Rheumatic disease and joint inflammation are common diseases in the community, especially in people aged 40 years and over. More than 40 percent of these age groups suffer from complaints of joint and muscle pain. This study aims to determine the experience of caregivers in caring for the elderly with chronic rheumatic disease in Buku Village, Mapilli sDistrict, Polewali Mandar Regency, West Sulawesi Province. . The method used in this sresearch is this research using qualitative research where this research is a method of inquiry to find answers to the elderly. The sample was 20 elderly respondents who were made as respondents. The results of the study were based on the results of the research on the understanding of caregivers in caring for the elderly with chronic rheumatic disease, there were 20 respondents who did the research.The results were the understanding of caregivers in caring for the elderly who lacked understanding as many as 2 people (10%) and good understanding of caregivers as much as 18 people (90%).